II. Danziger Internationale Messe : 3. bis 6. August 1924. (Danzig : [wydawca nieznany], 1924)
Folder informacyjny targów gdańskich.
Keywords: Targi -- Polska -- Gdańsk -- 1900-1945 -- druki ulotne; Gdańsk (Polska) -- 1920-1939 (Wolne Miasto) -- druki ulotne; Druki ulotne -- 1900-1945.